Implementación de un sistema contable en el banco comunal "San Bartolomé" de la parroquia de Belisario Quevedo, provincia de Cotopaxi. - Unaucho Quishpe, María Isolina (2020)
The present integrating project "Implementation of an Accounting System in the Bank Communal San Bartolomé of the parish of Belisario Quevedo, Province of Cotopaxi ” focused on the main objective that is the implementation of an accounting system, reliable, economic, safe and easy to handle that allows the correct recording of your assets, liabilities patrimonies and as established by the control body such as the superintendency of popular and solidarity economy, thus generating trust, transparency for each of its partners and customers; It will also be of vital importance when making decisions for part of the General Meeting of partners. With the implementation of this system, the problem detected with which the collection, organization and registration of all the information that is generated daily as a result of the activities of financial intermediation carried out by the institution, with the registration in the database; I know drew up the Daily Book, Ledger, Trial Balance, General Balance and Status Results, which served as fundamental tools for the proper management of the institutional resources that allow decision-making in the communal bank. The The methodology used in this project was quantitative because it allows the study of the detailed accounting information, analyzing the entire numerical part of the field economic and financial in order to meet the proposed objectives, and in the same way techniques and instruments such as: survey, interview and observation were applied, within and outside the institution